Factors affecting complaint behavior among motor vehicle repair service consumers in Shah Alam, Malaysia - Mat, Azmi (2013)
Understanding of consumer complaint behavior (CCB) is imperative in the present of competitive business environment as it serves as a quality improvement tool in order to enhance consumer satisfaction. This study aims to determine the factors influencing complaint behavior among motor vehicle repair and service consumers. Data was collected using self-administered questionnaire among 400 respondents who sent their cars for servicing at eight selected service centers representing four top car brands sold in the country for the year 2011. Those who had experienced a service failure within twelve months with the service center and were willing to participate in the study were selected. The respondents consisted of 60.8 percent female with an average age of 28.5 years old and majority had tertiary education level. The respondents experienced dissatisfaction with various types of dissatisfying episodes and prefer to lodge their complaints directly with the organization. Respondents’ attitude towards complaining was positive, with good knowledge of consumers' right but rather poor on technical matters related to car service. Among the demographic factors, only gender, education and occupation were found to influence CCB. All the three factors explored namely attitude, knowledge and personality were found to have positive relationship with CCB. All of them contributed significantly to predicting CCB with adjusted R²=0.1223, (F=11.271; p=0.001). This explained 12.23 percent of the variance in CCB with personality as the most influential factor. The results indicated that demographically, complainers are more likely to be female, better educated and worked in private sector. They were also found to be more assertive and exhibited greater self-confidence. Therefore, self-protection of consumers of motor vehicle repair and service could further be enhanced if that personality characteristic is accompanied with greater technical knowledge on complaint process. The service providers on the other hand should take the opportunity to rectify the dissatisfaction as they are given the opportunity to remedy the complaints and service failure. In addition, regulators or policy makers shall seriously look at the issues and undertake more effective regulatory measures to protect consumers. Government and its relevant agencies should strengthen the enforcement of the law such as Consumer Protection Act, 1999 and Pendedahan Maklumat Bengkel 2002, as well as to draft new policy or law since there is no other specific law to protect consumer in this industry.